Computer simulation of pyrolysis of rice hulls - David, Elsie M. (1986)
An attempt to use time series analysis on rice hulls pyrolysis data previously obtained by Festin, et. al. using a semi-continuous vertical converter failed. Product yields and experimental variables were not regularly monitored and runs were not long enough. Nevertheless, a time series model-identification program was developed for the only long run. Using linear regression instead, the effects of process temperature, air flow rate, amount of charge and run length on product yields and heating values were analyzed. A computer program, in which the developed models were incorporated., was used to simulate seven runs. Results showed that the simulated values for the total oil and gas yields were within 30% of the actual values. Failure of the models to account for the total char yield within this range was attributed to the fact that the char yield values were obtained by difference from the mass balance equation: char=feed+air-oil-gas, so that errors incurred in the computation were reflected in the char value. No statistically significant model was developed for char and oil heating values due to lack of data points. Optimum conditions for the production of gas, char and dry condenser oil were established for the data range of the investigation.